Particle image velocimetry measurements of a transitional boundary layer under free stream turbulence - Nolan, K; Walsh, E (2012)
High-speed particle image velocimetry (PIV) measurements of bypass transition reveal the breakdown of the ubiquitous streaks into turbulent spots. Individual streak velocity profiles are examined and contrasted with the root mean square profiles typically reported. An estimation of streak amplitude based on the modulation of the instantaneous boundary layer thickness is proposed. Examination of the PIV velocity fields shows how turbulent spot precursors, identified with concurrent hot-film recordings, consist of streamwise arrangements of positive and negative streaks. As secondary instability progresses, the interface between these streaks is observed to result in turbulent structures. In an attempt to further elucidate the role of the free stream turbulence, correlation maps are generated to determine the extent of the wall-normal fluctuations. Significant damping of the free stream is found within the boundary layer for all Reynolds numbers prior to the onset of spot precursors. © 2012 Cambridge University Press.